Determining nuclear shape: the role of farnesylated nuclear membrane proteins - Polychronidou, Maria; Großhans, Jörg (Nucleus, 2011)
Changes in nuclear morphology are observed in diverse developmental processes as well as in pathological conditions. Modification of nuclear membrane and nuclear lamina protein levels results in altered nuclear shapes, as it has been demonstrated in experimental systems ranging from yeast to human cells. The important role of nuclear membrane components in regulating nuclear morphology is additionally highlighted by the abnormally shaped nuclei observed in diseases where nuclear lamina proteins are mutated. Even though the effect of nuclear envelope components on nuclear shape has been thoroughly described, not much is known about the molecular mechanisms that govern these events. In addition to the known role of intermediate filament formation by lamins, here we discuss several mechanisms that might alone or in combination participate in the regulation of nuclear shape observed upon modification of the levels of nuclear membrane and lamina proteins. Based on recent work with the two farnesylated nuclear membrane Drosophila proteins, kugelkern and lamin Dm0, we propose that the direct interaction of farnesylated nuclear membrane proteins with the phospholipid bilayer leads to nuclear envelope deformation. In addition to this mechanism, we suggest that the interaction of nuclear membrane and lamina proteins with cytoskeletal elements and chromatin, and modifications in lipid biosynthesis might also be involved in the formation of abnormally shaped nuclei.